Linguistic Influences on Early Numerical Development: Pedagogical and Research Implications from a Scoping Review and Systematic Review - Tiaden, Insa-Annett Freyja (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2026)
This thesis explores the complex relationship between young children's acquisition of early numerical concepts and number-naming conventions in natural languages. Acknowledging that numeracy is fundamental for future academic performance and cognitive development, the thesis examines how the linguistic characteristics of a child's first language may help or interfere with their understanding of the base-10 system or cardinality, The research employed a sequential two-phase design: - Phase 1: Scoping Review. Using the Arksey and O'Malley framework, this phase mapped current literature to identify how linguistic variations, in particular transparency, inversion, and semantic singular/plural markers, influence number acquisition. This phase included a stakeholder consultation with mathematics practitioners. - Phase 2: Systematic Review. This phase evaluated the effectiveness of Differentiated Instruction (DI) as a pedagogical response to the variability created by these linguistic and cognitive factors, focusing on achievement and attitudes in primary and middle school students. The scoping review established that language-specific structures can significantly impact the pace and accuracy of numerical learning: - Transparency: Children speaking languages with transparent number naming system (e.g., Welsh or Vietnamese) can acquire counting and place-value concepts more rapidly than those speaking languages with opaque number naming systems (e.g., English or French). - Inversion: Languages with inverted number naming systems (e.g., German "one-and-twenty") can lead to higher frequencies of inversion errors during number estimation tasks. Semantic Sing/Pl Markers: The absence of semantic singular/plural markers in a language can impede the understanding of the cardinality principle, particularly the distinction between "one" and "many". The systematic review demonstrated that Differentiated Instruction could efficiently bridge the conceptual gaps caused by these linguistic features. Twelve empirical research' findings showed that DI consistently has a favourable effect on students' attitudes and mathematics achievement. Precise diagnosis, which is frequently made possible by adaptive technologies, and instructional scaffolding that is customised to each learner's unique cognitive profile have been recognised as critical success factors. In conclusion, this thesis indicates that language-sensitive mathematics instruction and the consistent use of DI can level the playing field, even though linguistic structures create distinct conceptual starting places for students. The results emphasise the need for teacher preparation programs and adaptable technologies to assist linguistically diverse classrooms, as well as a notable awareness gap among practitioners regarding linguistic influences.
APPROVED
Keywords: Number Naming Systems; Number Naming Conventions; Transparency; Inversion; Semantic Singular/Plural Markers; Scoping Review; Systematic Review; Number Naming; Differentiated Instruction; Early Numeracy; Base-10; Cardinality; Numerrical Concepts Acquisition; Language and Numerical Acquisition; Counting; Cardinality Principle; Number Line Estimation; Language-Sensitive Mathematics Instruction; Linguistic Diversity; Mathematical Achievement; Attitude towards Mathematics; Early Numerical Learning